Inositol Polyphosphate Multikinase Inhibits Angiogenesis via Inositol Pentakisphosphate-Induced HIF-1α Degradation. Issue 3 (2nd February 2018) - Fu, Chenglai; Tyagi, Richa; Chin, Alfred C.; Rojas, Tomas; Li, Ruo-Jing; Guha, Prasun; Bernstein, Isaac A.; Rao, Feng; Xu, Risheng; Cha, Jiyoung Y.; Xu, Jing; Snowman, Adele M.; et al.
Abstract : Rationale: : Inositol polyphosphate multikinase (IPMK) and its major product inositol pentakisphosphate (IP5) regulate a variety of cellular functions, but their role in vascular biology remains unexplored. Objective: : We have investigated the role of IPMK in regulating angiogenesis. Methods and Results: : Deletion of IPMK in fibroblasts induces angiogenesis in both in vitro and in vivo models. IPMK deletion elicits a substantial increase of VEGF (vascular endothelial growth factor), which mediates the regulation of angiogenesis by IPMK. The regulation of VEGF by IPMK requires its catalytic activity. IPMK is predominantly nuclear and regulates gene transcription. However, IPMK does not apparently serve as a transcription factor for VEGF. HIF (hypoxia-inducible factor)-1α is a major determinant of angiogenesis and induces VEGF transcription. IPMK deletion elicits a major enrichment of HIF-1α protein and thus VEGF. HIF-1α is constitutively ubiquitinated by pVHL (von Hippel–Lindau protein) followed by proteasomal degradation under normal conditions. However, HIF-1α is not recognized and ubiquitinated by pVHL in IPMK KO (knockout) cells. IP5 reinstates the interaction of HIF-1α and pVHL. HIF-1α prolyl hydroxylation, which is prerequisite for pVHL recognition, is interrupted in IPMK-deleted cells. IP5 promotes HIF-1α prolyl hydroxylation and thus pVHL-dependent degradation of HIF-1α. Deletion of IPMK in mouse brain increases HIF-1α/VEGF levels and vascularization. The increased VEGF in IPMK KO disrupts blood–brain barrier and enhances brain blood vessel permeability. Conclusions: : IPMK, via its product IP5, negatively regulates angiogenesis by inhibiting VEGF expression. IP5 acts by enhancing HIF-1α hydroxylation and thus pVHL-dependent degradation of HIF-1α. Abstract : Supplemental Digital Content is available in the text.